Heavy metal levels in plasma and fecal material samples of the black vulture (Coragyps atratus) - Bravo, Alfonso; Colina, Marinela; Azuero, Sandra; Salas, Rodolfo (Revista Científica de la Facultad de Ciencias Veterinarias)
The level of cadmium (Cd), copper (Cu), lead (Pb), vanadium (V), and zinc (Zn) were determined in blood plasma samples of healthy black vultures (Coragyps atratus) (n = 10). The correlation between metal levels in plasma samples and metal vs total plasmatic protein level, also calculated. Cd, Cu, Zn, Ni and Fe concentrations determined in a pooled sample of fecal material from the black vulture (n = 5) and compared with levels determined in a pooled sample of Hen fecal material (Gallus gallus domesticus) (n = 5). Metal levels determined through flame atomic absorption spectrophotometry (FAAS). Analysis of vulture plasma samples yielded concentrations (mg/L) of 7.25 Ó 3.01; 14.50 Ó 8.60; 6.85Ó4.85; 47.33 Ó 24.74 and 3.50 Ó 2.73, for Cd, Cu, Pb, V and Zn, respectively. No correlation established between plasmatic levels of the various metals, or between metals and total protein levels (P > 0.05). In vulture feces, metal levels (Î¼g/g) corresponded to 13.93 Ó 1.18; 20.26 Ó 0.41; 15.19 Ó 1.33; 4,823.76 Ó 8.99; and 202.57 Ó 1.65 for Cd, Cu, Ni, Fe, and Zn, respectively. In hen fecal samples, metal levels (Î¼g/g) corresponded to 38.85 Ó 0.70; 700.84 Ó 11.09; and 478.18 Ó 5.83, for Cu, Fe, and Zn, respectively. Under assay conditions Cd or Ni were not detected in hen feces. The physiological and environmental significance of elevated plasmatic and fecal metal levels in the black vulture, are discussed.